Effects of two different tapering protocols on fitness and physical match performance in elite junior soccer players - Krespi, M.; Sporiš, G.; Trajkovic, N. (The Journal of Strength and Conditioning Research, 2020)
The purpose of this study was to determine the effects of 2 different tapering protocols on fitness and physical match performance in elite junior soccer players. One-hundred fifty-eight elite junior soccer players (mean age: 17.1 ± 0.79 years; mean height: 177.9 ± 6.64 cm; mean body mass: 71.3 ± 7.96 kg; and mean body mass index: 22.5 ± 1.66 kg/m2) were randomly assigned to 2 groups: an exponential (n = 79) and a linear tapering (n = 79) group. Training sessions were conducted 3 times per week for 8 weeks. After 4 weeks of training and 4 weeks of tapering, participants were assessed in terms of body composition, physical fitness, and distance covered within a match. Both groups showed similar changes for body composition. The exponential group showed better improvement than the linear group in the 5- and 30-m sprints, countermovement jump, and VO2max (p < 0.05). The exponential tapering group had larger changes (p < 0.05) than the linear group in medium running (8-13 km/h) (6%; effect size = 0.26 compared with 5.5%; effect size = 0.22) and sprinting (>18 km/h) (26%; effect size = 0.72 compared to 21.7%; effect size = 0.60). The results show that exponential tapering produced better effects on speed, power, and endurance abilities than the linear protocol. Our results confirmed the reports of others that suggest that volume is the optimal variable to manipulate while maintaining both the intensity and the frequency of sessions.